A histopathological study on the Caucasian dwarf goby from an anthropogenically loaded site in Hungary using multiple tissues analyses. (29th February 2020) - Yancheva, Vesela; Georgieva, Elenka; Stoyanova, Stela; Velcheva, Iliana; Somogyi, Dóra; Nyeste, Krisztián; Antal, László
Abstract: The present study aimed to investigate for the first time the health status of the Caucasian dwarf goby Knipowitschia caucasica (Berg, 1916, Fishes of freshwaters of Russian Empire, p. 563, Moscow, Russia: Dep. Zemledeliya) (Teleostei: Gobiidae) from an anthropogenically loaded site in Hungary using histopathological analyses on multiple tissues. For that purpose, fish were collected from the public beach at Tiszafüred near the River Tisza. Gills, liver and kidney were subjected to histopathological analyses, and the results showed different alterations in each organ, which also differed in their extent and severity. In addition, we also found lesions in the reproductive organs of both, male and female fish which, overall, we hypothesized could be due to untreated municipal wastewaters, most likely contaminated with endocrine‐disrupting chemicals. The multi‐organ histopathological analyses of Caucasian dwarf gobies revealed different lesions, prevalence and severity in each target organ, as follows: liver>gills>kidney>gonad (testes and ovaries). These histopathological lesions can be assessed as good indicators of contamination by endocrine‐disrupting chemicals of freshwater ecosystems.